Analisis Kelayakan Usaha Kusen Beton, Roster Beton dan Kusen Beton - Fabella Budi , Ajeng; Nusantoro, Jawoto; Septiani, Ana (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to determine the business of concrete frames, concrete breezeblocks, and signpost lists of Donomulyo Bumi Agung Village East Lampung in terms of legal aspects, market and marketing aspects, technical and technological aspects, environmental aspects, HR aspects and financial aspects analyzed by Payback Period (PP), Net Present Value (NPV), Break Event Point (BEP), Average Rate of Return methods. The existence of concrete frames, concrete breezeblocks and signpost lists is needed for building construction. The use of concrete materials will make the building stronger and greatly beautify the building.